15th nordic-baltic conference on biomedical engineering and medical physics (NBC 2011) 14-17 June 2011, Aalborg, Denmark - Nordic-Baltic Conference on Biomedical Engineering and Medical Physics 2011 Aalborg, Denmark); Dremstrup, Kim.; Rees, Steve; Jensen, Morten Olgaard; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This volume presents the Proceedings of the 15th Nordic-Baltic Conference on Biomedical Engineering and Medical Physics. NBC 2011 brought together science, education and business under the motto Cooperation for health. The topics covered by the Conference Proceedings include: Imaging, Biomechanics, Neural engineering, Sport Science, Cardio-pulmonary engineering, Medical Informatics, Ultrasound, Assistive Technology, Telemedicine, and General Biomedical Engineering.
Imaging - Biomechanics - Neural engineering - Sport Science - Cardio-pulmonary engineering - Medical Informatics - Ultrasound.-  Assistive Technology - Telemedicine - General BME.
Electronic reproduction.
Keywords: Biomedical engineering -- Congresses; Medical physics -- Congresses; Electronic books